Soft Smooth Baby Skin - Dessai, Rupal (Homœopathic Links, 2014)
The remedy was selected based on the source words and quality of the source given by the patient, with an amazing recovery. This confirms that a remedy, especially a new remedy, can be reached in many other ways besides a conventional materia medica search and proving. Thanks to Alize Timmerman, this new remedy proving complemented the remedy selection. It was kindly sent from her clinic.
Keywords: Urticaria; Sarcodes; Amniotic fluid